Early Indian Architecture : Palaces - Coomaraswamy, Ananda K. (Brill | Manohar Publishers & Distributors, 2024)
Traditionally, Indian architecture is divided into sacred and royal structures. Palaces in the Indian subcontinent are the most important landmarks associated with Indian heritage. This slim volume focuses on the architectural features associated with prasada, or palace structures constructed during the ancient and medieval times. Coomaraswamy examines the features associated with palace structures such as pillars, walls, apartments, streets, gateways, quarters of the royal members, windows, arches, facades, etc., and the materials which were use for its construction. The author looks at both literary and archaeological evidences. The book also uses photographs and sketches of various palace structures located in Bharhut, Sanchi, Amravati, Mammallapuram, Bengal, and other parts of India to explain the features associated with Indian styles of palace construction. This book is highly recommended for students, archaeologists, and researchers interested in ancient and medieval Indian art and architecture.